Ventricular assist devices in transposition and failing systemic right ventricle: role of tricuspid valve replacement. (4th March 2022) - Gonzalez-Fernandez, Oscar; De Rita, Fabrizio; Coats, Louise; Crossland, David; Nassar, Mohamed S; Hermuzi, Antony; Santos Lopes, Bruno; Woods, Andrew; Robinson-Smith, Nicola; Petit, Thibault; Seller, Neil; O'Sullivan, John; et al.
Abstract: OBJECTIVES: Ventricular assist device (VAD) for systemic right ventricular (RV) failure patients post-atrial switch, for transposition of the great arteries (TGA), and those with congenitally corrected TGA has proven useful to reduce transpulmonary gradient and bridge-to-transplantation. The purpose of this study is to describe our experience of VAD in systemic RV failure and our move towards concomitant tricuspid valve replacement (TVR). METHODS: This is a single-centre retrospective study of consecutive adult patients receiving HeartWare VAD for systemic RV failure between 2010 and 2019. From 2017, concomitant TVR was performed routinely. Demographic, clinical variables and echocardiographic and haemodynamic measurements pre- and post-VAD implantation were recorded. Complications on support, heart transplantation and survival rates were described. RESULTS: Eighteen patients underwent VAD implantation. Moderate or severe systemic tricuspid regurgitation was present in 83.3% of patients, and subpulmonic left ventricular impairment in 88.9%. One-year survival was 72.2%. VAD implantation was technically feasible and successful in all but one. Post-VAD, transpulmonary gradient fell from 16 (15–22) to 10 (7–13) mmHg ( P = 0.01). Patients with TVR ( n = 6) also demonstrated a reduction in mean pulmonary and wedge pressures. Furthermore, subpulmonic left ventricular end-diastolic dimension (44.3 vs 39.6 mm; P = 0.03) and function improved in this group. After 1 year of support, 72.2% of patients were suitable for transplantation. CONCLUSIONS: VAD is an effective strategy as bridge-to-candidacy and bridge-to-transplantation in patients with end-stage systemic RV failure. Concomitant TVR at the time of implant is associated with better early haemodynamic and echocardiographic results post-VAD. Abstract : Systemic right ventricular (RV) failure, significant tricuspid regurgitation and clinical decompensation are common late complications following the atrial switch procedure for transposition of the great arteries (TGA) [1–6].